The Effect of Inclusion on Crack Propagation Using Extended Finite Element Method - Luthfi Muhammad Mauludin; Aji Pratama Rendragraha (Jurnal Internasional Penelitian Teknologi Terapan, 2022)
Numerical simulation is developed to investigate the effect of inclusion on crack propagation. In this study, the crack growth is modeled using extended finite element method (XFEM). Two-dimensional rectangular plate with single inclusion embedded off-centered is modeled. The specimen is subjected to uniaxial tension. The dimensions of the specimen are 40 mm x 80 mm and the radius of the inclusion is 10 mm. The specimen is pre-cracked with the length of an edge crack is 5 mm. The motion of the crack is modeled by XFEM based on traction-separation cohesive behavior for 2D mixed mode problem. In addition, enrichment procedure is used to implicitly determine predefined crack in XFEM framework. Two different inclusions, which are soft and hard inclusions, are considered on crack propagation scheme. The effects of soft and hard inclusions on crack propagation are studied and observed. The results showed that the trajectory of crack highly depends on inclusion inside the material. In the case of soft inclusion, propagation of the crack tended to approach the inclusion. Whereas in the case of hard inclusion, crack trajectory tended to move away from the inclusion. The mismatch of elastic modulus between inclusion and surrounded materials has significant effect on propagation of crack.